PENGARUH TINGKAT AKTIVITAS EKSPLORASI DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME PADA PERUSAHAAN PERTAMBANGAN - Feolina Rosiana; Sri Luayyi; Prima Noermaning Attarie (ICMA Nasional, 2023)
This research aims to determine the influence of the level of exploration activity and company size based on PSAK 64 on conservatism in mining sector companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2021 period. The level of exploration activity is measured using the exploration aggressiveness indicator, company size is measured using Ln (total assets), and conservatism using the Net Asset Measure (NAM).The sampling technique used is a non-probability sampling method, namely the purposive sampling method. The sample used in this research was 7 mining sector companies during the 2018-2021 period. Data for this research was collected using documentation techniques. Hypothesis testing is carried out using multiple linear regression analysis by first conducting a classical assumption test.The results of this research show that partially and simultaneously the level of exploration activity and company size based on PSAK 64 have a positive and significant effect on conservatism. High exploration costs do not necessarily indicate future economic benefits so they will affect the quality of profits generated and are thought to also reduce conservatism in financial reporting. Large companies will tend to report relatively permanent low profits using the principle of conservatism to avoid high tax burdens.